Peran Preceptor terhadap Ansietas Mahasiswa Praktik Klinik Terkait Penularan Penyakit Tuberkulosis Paru di Rumah Sakit - Sugiharno, Ramadhan Trybahari; Mulyanti, Mulyanti; Anouw, Neliana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between the role of the preceptor and the anxiety of clinical practice students in hospitals. This research method is quantitative, using a cross-sectional study design approach. The results of the study showed that there was a significant relationship between the role of preceptor, knowledge, and students' level of anxiety regarding TB transmission in hospitals with a p-value <0.05. In conclusion, there is a relationship between the role of the preceptor and the fear of clinical practice students in hospitals regarding the transmission of pulmonary TB. Keywords: Anxiety; Nursing, Student, Perceptor, Tuberculosis